Corrosion behavior of HPT-deformed TiNi alloys in cell culture medium - Awang Shri, Dayangku Noorfazidah; Tsuchiya, Koichi; Yamamoto, Akiko (AIP Publishing LLC., 2017)
In recent years there are growing interest in fabrication of bulk nanostructured metals and alloys by using severe plastic deformation (SPD) techniques as new alternative in producing bulk nanocrystalline materials. These techniques allows for processing of bulk, fully dense workpiece with ultrafine grains. Metal undergoes SPD processing in certain techniques such as high pressure torsion (HPT), equal-channel angular pressing (ECAP) or multi-directional forging (MDF) are subjected to extensive hydrostatic pressure that may be used to impart a very high strain to the bulk solid without the introduction of any significant change in overall dimension of the sample. The change in the structure (small grain size and high-volume fraction of grain boundaries) of the material may result in the corrosion behavior different from that of the coarse-grained material. Electrochemical measurements were done to understand the corrosion behavior of TiNi alloys before and after HPT deformation. The experiment was carried out using standard three electrode setup (a sample as working electrode; a platinum wire as a counter electrode and a saturated calomel electrode in saturated KCl as a reference electrode) with the surface area of 26.42 mm2 exposed to the EMEM+10% FBS cell culture medium. The measurements were performed in an incubator with controlled environment at 37 °C and 5% CO2, simulating the cell culture condition. The potential of the specimen was monitored over 1 hour, and the stabilized potential was used as the open-circuit potential (EOCP). Potentiodynamic curves were scanned in the potential range from −0.5 V to 1.5 V relative to the EOCP, at a rate of 0.5 mV/s. The result of OCP-time measurement done in the cell culture medium shows that the OCP of HPT-deformed samples shifts towards to the more positive rather than that of BHPT samples. The OCP of deformed samples were ennobled to more than +70 mV for Ti-50mol%. The shift of OCP towards the nobler direction indicates the passive nature of native oxides formed on the surface of the samples. The polarization curve, on the other hand, indicates that the HPT deformation was found to shift the passive current to nobler region. The passive region current density is found to be lower than that of the BHPT, suggesting the passive film formed on the surface of HPT-deformed samples is more protective than that of the BHPT sample. This study has shown that nanocrystallization and amorphization induced by severe plastic deformation change the corrosion behavior of TiNi alloys.